National Recovery and Resilience Plan and Health: qualitative analysis on the sustainability of the interventions on healthcare - Cascini, F.; Gentili, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Sars-CoV2 epidemic was the cause of death of more than 180,000 Italian citizens. The severity of this disease showed to policymakers how easily Italian health services, and particularly hospitals, could be overwhelmed by requests and needs from patients and the general population. As a consequence of the clogging of health services, the government decided to allocate a consistent investment to the community and proximity assistance with a specific section (Mission 6) of the so called “National Recovery and Resilience Plan”.Objective. The aim of this study is to analyse the economic and social impact of the Mission 6 of the National Recovery and Resilience Plan, with particular regard to the most relevant interventions (Community Homes, Community Hospitals, Integrated Home Care), in order to understand its future sustainability.Material and methods. A qualitative research methodology was chosen. Documents containing all the relevant information regarding the sustainability of the plan (called in short “Sustainability Plan”) were taken into consideration. In case of missing data regarding the potential costs or expenditure of the aforementioned structures, estimates will be made reviewing literature for similar healthcare services, already implemented and active in Italy. Direct content analysis was chosen as the methodology for data analysis and final reporting of results.Results. The National Recovery and Resilience Plan states that it will create savings of up to €1.18 billion thanks to the re-organization of healthcare facilities, the reduction of hospitalizations, the reduction of inappropriate access to the emergency room, and the containment of pharmaceutical expenditure. This amount will be used to cover the salaries for the healthcare professionals employed in the newly planned healthcare structures. The analysis of this study has taken into account the number of healthcare professionals that will be needed to operationalize the new facilities, as described in the plan and compared them with the reference salaries for each category (doctors, nurses, other healthcare workers). The annual cost for healthcare professionals has been stratified for each structure, with the following results: € 540 million for the personnel of the Community Hospitals (“Ospedali di Comunità”); € 1.1 billion for the personnel of Integrated Home Care Assistance (“Assistenza Domiciliare Integrata”); and € 540 million for the personnel of Community Homes (“Case della Comunità”).Discussion. The expected € 1.18 billion expenditure is implausible to be sufficient to cover the cost for salaries of all the healthcare professionals needed, which is expected to be around € 2 billion. The National Agency for the Regional Healthcare Services (“Agenzia nazionale per i servizi sanitari regionali”) calculated that in Emilia-Romagna (the only region in Italy to have already implemented a healthcare structure based on the one described in the National Recovery and Resilience Plan), the activation of Community Hospitals and Community Homes reduced the rate of inappropriate access to emergency rooms by 26% (while in the National Recovery and Resilience Plan expectation is a reduction of at least by 90% for “white codes”, the identified code for stable and not urgent patients). Moreover, the hypothesis for the daily cost of stay in the Community Hospital is roughly € 106, while the average current cost in the active Community Hospitals in Italy is € 132 (much higher than the National Recovery and Resilience Plan estimate).Conclusion. The underlying principle of the National Recovery and Resilience Plan is highly valuable since it strives to enhance the quality and the quantity of the healthcare services in the country that are too often left out of national investments and programs. Nevertheless, the National Recovery and Resilience Plan has critical issues due to the superficial prevision of cost. The success of the reform appears to be established by decision makers and by their long-term prospective, oriented to overcome the resistance to change.